IDENTIFIKASI MORFOLOGI DAN ANATOMI JERUK LOKAL (Citrus sp) DI DESA DODA DAN DESA LEMPE KECAMATAN LORE TENGAH KABUPATEN POSO - Adelina, Surya Oktafia; Adelina, Enny; Hasriyanty, Hasriyanty (AGROTEKBIS, 2017)
This study aims was to determine the characteristics of citrus plants basedon theirmorphology and anatomy of leafat Dodaand Lempe Villages, Lore Tengah District-Poso Regency. The observation of morphologywas conducted in the field in both villages, while the anatomical observation was conducted at Science and Seed TechnologyLaboratory and Pest and Disease Laboratory of Agriculture Faculty of Tadulako University from October to November2015.The morphology variable observed was the shape and color of the trunk, branching form, canopy,canopydiameter, trunk surface, leaf adges and ends shape, leaf symmetry, flus color, leaf upper and upper and lower surface, leaf mesophyl, leaf size, petiole shape and length. The anatomy consist of density and stomata index. The result showed that morphology and anatomy characteristics observed based on cluster analysis drawn in the shape of dendogram. The results of cluster analysis was obtained that the citrus in both villages has two or three accessions, this initial finding can be used later to discover good quality of citrus seedling.Keywords: Citrus Anatomy, Dendogram, and Morphology.